2022
DOI: 10.1155/2022/9866111
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Detection of H2O2 on Graphene Nanoribbons/Cobalt Oxide Nanorods‐Modified Electrode

Abstract: The most important biological changes which have to be monitored is the mechanism of ageing in the human body where the mitochondria play a major role. Hydrogen peroxide (H2O2) is one of the important markers for the reactive oxygen species (ROS), which denatures the protein and DNA, that was the main contributory factor of ageing. So, it is very important to monitor H2O2 levels in the biological samples. Herein, we reported the preparation of 1D graphene nanoribbon/cobalt oxide nanorod (GNR/Co3O4) based nanoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Preparation of GNR/MnO 2 Nanocomposite. First, GNRs were prepared as reported elsewhere [33]. From the obtained powder, dispersion of GNRs was prepared with the concentration of 1.5 mg/mL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation of GNR/MnO 2 Nanocomposite. First, GNRs were prepared as reported elsewhere [33]. From the obtained powder, dispersion of GNRs was prepared with the concentration of 1.5 mg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…GNR is a 1D material which has been used in the development of battery, supercapacitor, and sensors [32]. Recently, the GNR/Co 3 O 4 nanocomposite-based sensor was prepared for the selective detection of H 2 O 2 [33] and also oxidized GNR showed a good charging capacity of 1,400 mA hr/g in lithium-ion storage [34]. GNR-based sensors were also used to determine epinephrine [32] and nitrogen dioxide [35].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the electrochemical study revealed that the electrode with the GNR/Co 3 O 4 coating had a good electrocatalytic activity for the oxidation of H 2 O 2 at 0.925 V. From 10 to 200 M, this sensor responded linearly to H 2 O 2 oxidation. According to calculations, the LOD is 1.27 M [172]. The use of oxygen plasma treatment, which produces oxygenated functions, edge plane sites, and defects, has improved the performance of graphene-based electrochemical sensors.…”
Section: Applicationsmentioning
confidence: 99%
“…Its chemical and electrochemical stability ensures sensor reliability and longevity. Moreover, the cost-effectiveness of Co 3 O 4 and its abundance make it practical for large-scale sensor production [ 70 ]. Additionally, high surface area, achievable through nanostructuring, facilitates increased interaction with analytes, resulting in heightened sensitivity and responsiveness in H 2 O 2 detection.…”
Section: Introductionmentioning
confidence: 99%